THE ECOLOGICAL HOSTS SHIFT OF PARASITES AND THE OUTBREAK OF EMERGING INFECTIOUS DISEASES: A REVIEW - Legas, Mohammed Seid (International Journal of Research -GRANTHAALAYAH, 2017)
Parasites are organisms which metabolically depend upon their hosts. To understand the ecological host shift of a parasite, it is important to look the host-parasite associations with respect to ecological change and factors that generate, maintain, and constrain the associations with implications for a wide range of ecological issues, including the dynamics of emerging infectious diseases. Although, the ecological significance of parasites is almost overlooked for several years by ecologists, considerable efforts are being made to understand their functional importance in ecosystems. Parasites play vital role in the trophic cascades of the food web. Environmental change caused by anthropogenic activities result host shift of specialist parasites and this shift of specialized parasites can rapidly to new hosts via ecological fitting play an important role in the ecology and evolution of host-parasite associations. This condition is the primary cause for the Emerging Infectious Diseases when parasite species begin infecting and causing disease in host species with which they have no previous history of association. Therefore, understanding the host parasites interaction and distribution of known and potential pathogens is a vital precondition for optimizing their positive, while minimizing their negative effects on conservation, restoration and sustained development programs.